Dearomatization of 3‐Nitroindoles by a Phosphine‐Catalyzed Enantioselective [3+2] Annulation Reaction. Issue 16 (14th March 2019) - Li, Kaizhi; Gonçalves, Théo P.; Huang, Kuo‐Wei; Lu, Yixin
Abstract: The dearomatization of 3‐nitroindoles through a chiral‐phosphine‐mediated [3+2] annulation reaction is described. This method makes use of readily available 3‐nitroindoles as an aromatic feedstock and rapidly delivers a wide range of cyclopentaindoline alkaloid scaffolds in a highly enantioselective manner. Notably, phosphine‐triggered cyclization has not been utilized previously in a dearomatization process. Abstract : A disruptive influence : Variously substituted 3‐nitroindoles underwent dearomatization in a phosphine‐catalyzed asymmetric [3+2] annulation reaction with allenoates (see scheme). This method makes use of 3‐nitroindoles as a readily available aromatic feedstock and provides access to a wide range of cyclopentaindolines in a highly enantioselective manner.